Infectious clone–based dissection of delayed pathogenicity and evolutionary dynamics of Papaya leaf curl Guangdong virus (PaLCuGdV) - Renshu Huang; Muhammad Arif; Amna Saeed; Cheng Song; Omer Beyhan; Muhammed Said Yolcu; Islem Abid (European Journal of Plant Pathology, 2026)
Papaya leaf curl Guangdong virus (PaLCuGdV) is an economically significant begomovirus, although its pathogenicity and evolutionary dynamics are poorly understood. This study involved the construction of a full infectious clone of PaLCuGdV, which was agroinoculated into Nicotiana benthamiana ( N. benthamiana ) to assess the infectivity and symptomatology. The infectious clone elicited typical begomoviral symptoms just at 28 days post-inoculation, signifying delayed pathogenicity. Infection efficiency varied with strain, with successful transmission achieved using Agrobacterium GV301, but not with EHA105 alone. Southern blot analysis confirmed active viral DNA replication solely in diseased plants. Comparative sequencing and recombination analysis identified numerous recombination events among worldwide PaLCuGdV isolates, with the newly defined strain serving as a primary recombinant progenitor. These findings indicate that PaLCuGdV displays delayed symptom expression, strain-specific infectivity, and evolutionary diversity driven by recombination, underscoring the value of infectious clone systems for functional and evolutionary studies of begomoviruses.